Association Between Recurrence Rates of Colorectal Cancer and Carcinoembryonic Antigen Levels, Histopathological Features, Tumor-Infiltrating Lymphocytes, and Lymphatic Invasion at H. Adam Malik Central General Hospital, Medan - Mohammad, Fawzan; Muhar, Adi Muradi; Siregar, Edwin Saleh (The Indonesian Journal of General Medicine, 2024)
Introduction: In Indonesia, colorectal cancer ranks fourth in cancer incidence, with an estimated over 30,000 new cases each year. This study aims to investigate the association between colorectal cancer recurrence rates and CEA levels, histopathology, tumor-infiltrating lymphocytes, and lymphatic invasion at H. Adam Malik Central General Hospital, Medan. Methods: This cross-sectional study investigates the correlation between colorectal cancer recurrence and clinical parameters such as CEA levels, histopathology, TIL, and lymphatic invasion using retrospective data from patients at H. Adam Malik Central General Hospital in North Sumatra. Results:  Out of 75 patients identified, 45 met the inclusion criteria. The study found significant relationships between recurrence and CEA levels (p=0.007), histopathological grade (p<0.001), and lymphovascular invasion (p=0.026), while tumor-infiltrating lymphocytes showed no significant correlation (p=0.358). Conclusion: Colorectal cancer recurrence are primarily shown in male patients with rectal and sigmoid tumors, predominantly adenocarcinoma at stage IIb. Significant CEA levels, moderate histological differentiation, tumor-infiltrating lymphocytes, and lymphovascular invasion were identified.